ANALISIS EFISIENSI BANK UMUM SYARIAH DI INDONESIA PERIODE 2010-2012 - Tuzuhroh, Fatimah (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research is to explain the level of efficiency Islamic Banks in Indonesia period 2010-2012. This research analysis use a non parametric approach is DEA. The samples in this study were eleven Islamic Banks. The results of this study indicate that the majority of Islamic Banks only one experiencing Islamic Banks are always efficient during the period 2010-2012 namely Bank Maybank Syariah. Key words: The level of efficiency Islamic Banks, Islamic Banks, DEA